2018
DOI: 10.1016/j.aller.2017.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to dogs but not cats is associated to a decrease in the prevalence in atopic dermatitis amongst school-children

Abstract: Our findings suggest that exposure to dogs, whether they be indoor or outdoor pets, is associated to a decreased prevalence in atopic dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Table 1 summarizes the studies included in this review [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 summarizes the studies included in this review [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our review, all the articles included explored the association between prenatal, natal, and/or infancy (1–2 years of life) exposure to cat and dog hair and the development of allergy and/or asthma in preschool and/or school-aged children [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. Eight articles [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 ] investigated these outcomes in preschoolers.…”
Section: Resultsmentioning
confidence: 99%
“…With regard to pet dander allergens and AD, it has been previously observed that exposure to dogs, but not cats, may decrease the risk of developing AD . However, a cross‐sectional study of AD cases and controls from Hungary found that the odds of having AD were significantly higher in children that had indoor‐kept pets .…”
Section: Discussionmentioning
confidence: 99%
“…Cat and dog allergens are commonly found in public places and around 90% of homes in the United States have measurable levels of these allergens whether the home has ever had a furred pet living in it or not 17 . The studies exploring the association between pets and atopic diseases have been contradictory so far 18,19 . Though, systematic reviews have reported reductions in the risk of atopic diseases among children with close contact with animals (farm animals or indoor pets) during infancy 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“… 17 The studies exploring the association between pets and atopic diseases have been contradictory so far. 18 , 19 Though, systematic reviews have reported reductions in the risk of atopic diseases among children with close contact with animals (farm animals or indoor pets) during infancy. 20 , 21 , 22 However, regarding AD some studies have found a protective association of pets, 23 and others studies with adjustment for avoidance behavior have not found this association.…”
Section: Discussionmentioning
confidence: 99%